Apoptosis-related gene expression induced by Colombian propolis samples in canine osteosarcoma cell line - Pardo-Mora, Dolly Patricia; Murillo, Oscar Julián; Rey-Buitrago, Mauricio; Losada-Barragán, Mónica; Uribe, Jaime Fabian Cruz; Santiago, Karina Basso [UNESP]; Conti, Bruno José [UNESP]; de Oliveira Cardoso, Eliza [UNESP]; Conte, Fernanda Lopes [UNESP]; Gutiérrez, Rafael María; García, Orlando Torres; Sforcin, José Maurício [UNESP] (Veterinary World, 2021)
Background and Aim: Osteosarcoma (OSA) is the most common bone tumor in canines and humans. This study aimed to assess the cytotoxic and apoptotic effects of Colombian propolis samples on a canine OSA cell line (OSCA-8) by evaluating the expression of BCL-2, BAX, CASPASE 9, CASPASE 8, and TNFR1 genes involved in the apoptosis pathway. Materials and Methods: After treating the cells with five Colombian propolis samples (Usm, Met, Fus, Sil, and Caj), we evaluated cell viability and lactate dehydrogenase (LDH) release. Early and late apoptosis was determined by flow cytometry using annexin V/propidium iodide. Furthermore, the effects of three selected samples on gene expression were analyzed by real-time polymerase chain reaction. Results: The Colombian propolis samples reduced OSCA-8 cell viability and increased LDH release. All samples induced apoptosis significantly and upregulated BCL-2 and CASPASE 8 expression. Usm and Sil increased BAX expression, Met and Sil induced CASPASE 9 expression, and Usm increased TNFR1. Conclusion: Colombian propolis samples exhibited cytotoxic and apoptotic effects on canine OSA cells, and CASPASE 8 upregulation indicated apoptosis induction by the extrinsic pathway.
Keywords: Apoptosis; Cytotoxicity; Osteosarcoma; Propolis